Factors associated with deliberate self-harm method among patients in a tertiary hospital in South Africa - Pieterse, Deirdre (Department of Psychiatry and Mental Health, 2019)
Background: Hospital-based research provides important insight into the burden of suicide behaviour and methods used in deliberate self-harm (DSH). The information on methods used in DSH may be useful to plan suicide-related intervention and prevention programmes. We aimed to investigate the socio-demographic and clinical factors associated with the methods used in DSH at a tertiary hospital in Cape Town, South Africa. Methods: Socio-demographic, clinical and treatment data were collected from 238 consecutive DSH patients who presented for emergency department treatment at the hospital. Univariate analyses and a logistic regression model were used to explore the associations between these variables and violent and non-violent method of DSH. Results: Self-poisoning was the most common method of self-harm (80.3%, n=191). Prescription medication was the most common form of self-poison (57.6%, n=137) while a large number of patients used the non-prescription medication paracetamol (40.9%, n=54). In the bivariate regression analysis, male gender, stating that the reason for DSH was to escape a situation and history of substance use were associated with violent method of DSH. Conclusion: This study contributes to emerging literature on methods used in DSH in South Africa. There is an urgent need to improve monitoring of prescription medication commonly used in DSH. More research on the source of prescription medication and its relationship to DSH is needed. Limiting the quantity and reviewing the packaging of paracetamol available in supermarkets may be effective strategies of means restriction that could be adopted in South Africa. This study underscores the need for increased collaboration between the Department of Social Development and the Department of Health in providing substance use interventions to high-risk population groups.